PENGAWASAN TANDA DAFTAR PERUSAHAAN FINANCE DI KOTA PEKANBARU - Monica, Lusiana; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Increasingly the center of trade in services in the city of Pekanbaru making finance companies spread in the city of Pekanbaru. So many finance company located in Pekanbaru city does not have a company registration certificate. It is necessary to do the supervision by the Department of Trade and Industry and the BPT-PM Pekanbaru. Supervision is done so that deviations against illegal enterprises can be overcome. This research was conducted in order to finance companies in the city of Pekanbaru has thus ensuring the legality of the company and be able to increase revenue.The researchers used the theory Manullang, where quality of service is determined by establish standards, action assessment, and take corrective action. This study used descriptive qualitative method, data collection through observation and interviews in which the parties - the parties involved in this study as an informant.The results of this study indicate that the Department of Industry and Trade and the BPM-PM Pekanbaru have a good standard of supervision of the number of surveillance teams, but it is still a lack of socialization to the finance company owners, and there will be supervision and sanctions from the government if the finance is still against the rules. Factors that memghambat oversight is the lack of coordination between the Department of Industry and Commerce with BPT-PM, lack of awareness and knowledge of finance owner to register his company.Keywords: Controlling, Certificate of Company Registration, Enterprise, Finance.